Weak α-skew Armendariz ideal - Nikmehr, M. J.; Pazoki, M.; Tavallaee, H. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We introduce the concept of weak α-skew Armendariz ideals and investigate their properties. Moreover, we prove that I is a weak α-skew Armendariz ideal if and only if I[x] is a weak α-skew Armendariz ideal. As a consequence, we show that R is a weak α-skew Armendariz ring if and only if R[x] is a weak α-skew Armendariz ring.